Poor health-related quality of life prior to ECT in depressed patients normalizes with sustained remission after ECT - McCall, W. Vaughn (2012)
BACKGROUND: Health-related quality of life (HRQOL) is diminished in depressed adult outpatients and especially impaired among depressed patients referred for ECT. We compare pretreatment HRQOL in ECT and non-ECT depressed patients from two large samples, and examined whether sustained remission in depressive symptoms after ECT is associated with normalization of HRQOL. METHODS: HRQOL was measured with the Medical Outcomes Study Short Form 36 (SF36) before ECT and 6 months after ECT in an effectiveness (n=286) and an efficacy (n=243) clinical trial. RESULTS: ECT patients had very low baseline SF36 scores. With one exception, SF36 subscale scores in both trials were significantly lower than those of depressed outpatients. A minority of patients in both trials entered and sustained remission over the 24 week timeframe. Among sustained remitters, average SF36 scores were no different from normative scores of the general adult population, except that in the effectiveness study ECT patients reported less Bodily Pain (p<0.05) and better Mental Health (p<0.05), while in the efficacy study ECT patients reported more difficulty with Role-Emotional. (p<0.01) LIMITATIONS: Only a modest number of patients were observed in sustained remission. CONCLUSIONS: HRQOL is very poor in patients referred for ECT. Depressed patients who experience sustained remission after ECT, however, can expect improvement in their quality of life that leaves many in a position indistinguishable from the general adult population.